ARE THEY ALSO MIND COLONIZERS? EXPLORING THE ASSOCIATION BETWEEN GUT MICROBIOTA AND DEPRESSION (FUDMA JOURNAL OF SCIENCES, 2020)
The association of the gut microbiota with many diseased and healthy state is currently of global interest.  Depression is a disorder that is etiologically heterogeneous. There is a correlation between gut microbiota, immune responses, behaviour and pathophysiology of depression. These shows the link of microbiome and mental health, which point to a possible future of manipulation of gut microbiota for better health. This mini review compiled some existing literature on the relationship between depression and human gut microbiota.
Keywords: Gut microbiota; brain; depression